Incidence, prevalence, and survival of prostate cancer in the UK - Tan, EH; Burn, E; Barclay, NL; Delmestri, A; Man, WY; Golozar, A; Serrano, ÀR; Duarte-Salles, T; Cornford, P; Prieto Alhambra, D; Newby, D (American Medical Association, 2024)
Importance Incidence, prevalence, and survival are pertinent measures to inform the management and provision of prostate cancer care.